Investigating Rural Teachers' Professional Development, Instructional Knowledge, and Classroom Practice - Todd A. Glover; Gwen C. Nugent; Frances L. Chummey; Tanya Ihlo; Edward S. Shapiro; Kirra Guard; Natalie Koziol; Jim Bovaird (Journal of Research in Rural Education, 2016)
Teachers Speak was a national survey study designed to investigate the characteristics of rural elementary school teachers' existing professional development; differences in professional development practices between rural and non-rural settings; and the potential infl uence of professional development characteristics on rural teachers' knowledge, perceptions, and instructional practice. The respondents included 268 rural and 327 non-rural (city, suburban, town) teachers whose schools were selected via stratifi ed random sampling. Key fi ndings indicate that professional development experiences, perceptions, and classroom practices were similar for rural and non-rural teachers. Rural teachers did not appear to be comparatively disadvantaged, at least not in terms of their best professional development experiences. They reported comparable characteristics for professional development (e.g., providers, hours, practice and feedback opportunities, collaboration opportunities). An emphasis on topics during professional development was found to be related to increased (a) positive perceptions of the utility of the topics, (b) perceptions of knowledge gained pertaining to those topics, and (c) increased focus on those topics during classroom instruction. Perceived utility of instructional topics was a signifi cant predictor of reported practice. When including both rural and non-rural teachers, time in professional development was found to be a signifi cant predictor of their pedagogical content knowledge.